2006
DOI: 10.1186/1471-2407-6-12
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the interaction of extracellular matrix and phenotype of bladder cancer cells

Abstract: BackgroundThe extracellular matrix has a major effect upon the malignant properties of bladder cancer cells both in vitro in 3-dimensional culture and in vivo. Comparing gene expression of several bladder cancer cells lines grown under permissive and suppressive conditions in 3-dimensional growth on cancer-derived and normal-derived basement membrane gels respectively and on plastic in conventional tissue culture provides a model system for investigating the interaction of malignancy and extracellular matrix. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
(29 reference statements)
1
22
0
Order By: Relevance
“…The findings confirm our previous hypothesis that the ECM exerts a suppressive effect in vivo based on loss of malignant properties on SISgel in vitro [23]. The suppressive effect of SISgel is not due to the dominant protein, collagen I, or to absence of some factor in SISgel necessary for malignant grown because tumors formed with co-injected collagen I grew nearly as well as they grew when co-injected with Matrigel.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings confirm our previous hypothesis that the ECM exerts a suppressive effect in vivo based on loss of malignant properties on SISgel in vitro [23]. The suppressive effect of SISgel is not due to the dominant protein, collagen I, or to absence of some factor in SISgel necessary for malignant grown because tumors formed with co-injected collagen I grew nearly as well as they grew when co-injected with Matrigel.…”
Section: Discussionsupporting
confidence: 89%
“…Earlier research in our labs suggested that, unlike mammary epithelial cells, α6β4 integrins were not involved [24]. Microarray and proteomic studies implicated complex networks involving TGFβ, cMYC and a series of transcription factors [23], [25], [26]. Because a consistent gene signature could not be identified, it is likely that a protein switch regulates the conversion between the malignant and suppressed phenotypes.…”
Section: Discussionmentioning
confidence: 84%
“…Like spheroids, the MCL can be used to study the effects of growth conditions, ambient oxygen levels, media glucose concentration, or other media factors on tumor oxygen metabolism. In addition, the impact of different growth substrates on tumor oxygen consumption can be studied in the MCL, since, unlike spheroids, MCL form a 3-D layer of parenchyma on an underlying extracellular matrix, which has been shown to impact tumor phenotype (Birgersdotter et al, 2005,Dozmorov et al, 2006. Another powerful use of the MCL model involves combining quantitative oxygenation and drug transport studies.…”
Section: Possible Applications Of the Modelmentioning
confidence: 99%
“…First, it would likely expand the number of tumor cell lines that could be studied in vitro. Second, the impact of different types of extracellular matrix on tumor metabolism could be investigated, since, unlike spheroids, MCL grow on an underlying substrate, and extracellular matrix has been shown to influence tumor phenotype (Birgersdotter et al, 2005,Dozmorov et al, 2006. Third, it would permit drug transport and oxygenation to be quantitatively studied in the same in vitro model, which would be valuable for drugs whose uptake is known to be oxygen dependent (Hicks et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In urothelial carcinoma of the bladder (UC), the role of ECM proteins has been widely studied to assess invasive behavior. Gene expression in bladder cancer cell lines has been shown to depend on the matrix used for cultivation (Deen et al 1994; Ioachim et al 2005; Dozmorov et al 2006). The following review will focus on the role of structural proteins in UC, which have been suggested to be of prognostic value (Table 1).…”
Section: Introductionmentioning
confidence: 99%